THE "LARGE BARYON PUMP OF THE EARTH" AS A NATURAL IMAGE OF THE "TREE OF LIFE" AND AN OBJECT OF ENVIRONMENTAL LAW, WHICH IS INTEGRATED WITH THE NATURAL ENVIRONMENT OF MAN - Mykhaylo O. Baymuratov; Volodymyr P. Ozhereliev (Alfred Nobel University Journal of Law)
The article is devoted to the scientific and theoretical substantiation of the problem of defining the Great Baryon Pump of the Earth (GBP of the Earth) as a natural prototype of the "tree of life" and an object of environmental law that is integrated with the natural human environment. It is indicated that the authors of the article had previously investigated the issue of the relationship between the "right [of man] to the tree of life" and the biological rights of man, simultaneously touching on another important humanitarian and at the same time civilizational and legal issue - the identification of the so-called "GBP of the Earth" as material and natural prototype of the biblical metaphorical way of "tree of life". However, an even more important issue in the context of this study, which precedes this issue, is the qualification of the Earth's natural environment as an ecological object that is integrated with the natural habitat of man (his natural environment). It is proven that, according to the data of geological sciences, the GBP of the Earth in the process of rotation of the Earth on its axis, transforms the tangential acceleration (the component of acceleration directed along the tangent to the trajectory of the material point, which characterizes the change in the velocity module. – author) into radial (normal) acceleration, which explains the formation of vortex tracks on the lithosphere and pushing the Moon into a higher orbit relative to the Earth. Extrapolating its dynamics to 4.0 billion years ago - in the early eons of our planet, taking into account objective scientific data on the transformation of substances in the system of geospheres, it can be assumed that the GBP of the Earth was able to transform inanimate matter into living matter. This became a more significant and revolutionary factor, which was directed to the formation of an actor (acting subject) for the beginning of biological evolution and created the conditions for the emergence of man on Earth. In turn, the need to study the functions of the Earth's natural resources in the environmental discourse and its qualification as an object of law is a natural stage in the development of the system of ecological, noospheric law, and in the future - anthropic law as a metasystem of the natural law of our universe. Therefore, it is stated that the existence GBP of the Earth is inextricably linked with the concept of the anthropic properties of the space of our Universe in the light of the Poincaré-Perelman theorem, according to which "any single-connected closed three-dimensional manifold without an edge is a homeomorphic (continuous reversible transformation of space. – author) of the three-dimensional sphere". This theorem indicates the integrity, continuity and unbreakability of the space of our Universe from the moment of the so- called "Big Bang" (or another event similar to it) onwards: the formation of our Galaxy, the Solar System, the Earth-Moon system, the emergence of living matter, the beginning of biological evolution, the formation of Earth Man and the formation of the noosphere. On the other hand – in a functional bioecological context, the GBP of the Earth can be considered not only as an Eozoic (life-creating) object, but also as an actor that controls the continental cycle – continental drift, which is associated with the formation of the single continent of Pangea and its subsequent disintegration to separate continents. It is characteristic that in the process of geographical discoveries and human development of the global natural environment (environment), this led to the emergence of a modern picture of the world and the formation of a "topological two-circuit – shell-nuclear informational and legal structure of the noosphere". These events of the border of the XV-XVI centuries and the development of the colonial system determined the vector of the next evolution of the geopolitical landscape – its legal structuring, which, in accordance with the Legal Triad (order – rules – law) and the doctrine "rule based international order", was embodied in the picture of the modern world order. Currently, the world structure that has emerged can be imagined as a complex global-regional legal system, in the regulatory field of which there is a process of deep integration of international public law and municipal law. In turn, this has formed stable trends that indicate the active development of value ideas about biological human rights, as well as their implementation on a global scale. It is stated that the strategic goals, the achievement of which is important for the biologization of law, cannot be achieved without the identification of the Earth's natural reserve as a prototype of the "tree of life" object, and the qualification of the Earth's natural reserve as an Eozoic object that is integrated with the surrounding natural environment man (his natural environment). In addition, the resolution of the natural-law conflict that has arisen is absolutely necessary for the development of the system of international environmental law, the formation of the system of noospheric law, as well as the improvement of IL-forecasting methods in the process of strengthening the trends of global constitutionalism, noospherism and the development of the institute of biological human rights in the world civilizational legal system.